Value of Surgery and Nonsurgical Approaches for Cervical Spondylotic Myelopathy: WFNS Spine Committee Recommendations - Parthiban, J (2019)
OBJECTIVE: Cervical spondylotic myelopathy (CSM) has become a prevalent cause of spinal cord dysfunction among the aging population worldwide. Although great strides have been made in spine surgery in past decades, the optimal timing and surgical strategy to treat CSM have remained controversial. In this article the authors aimed to analyze the current trends in studies of CSM and to summarize the recent advances of surgical techniques in its treatment. METHODS: The PubMed database was searched using the keywords pertaining to CSM in human studies that were published between 1975 and 2018. Analyses of both the bibliometrics and contents, including the types of papers, authors, affiliations and countries, number of patients, and the surgical approaches were conducted. A systematic review of the literature was also performed with emphasis on the diagnosis and treatment of mild CSM. RESULTS: A total of 1008 papers published during the span of 44 years were analyzed. These CSM studies mainly focused on the natural history, diagnosis, and treatment, and only a few prospective randomized trials were reported. For the authors and affiliations, there was a shift of clustering of papers toward Asian countries in the past decades. Regarding the treatment for CSM, there was an exponential growth of surgical series published, and there was a trend toward slightly more anterior than posterior approaches through the past decade. Patients with CSM had increased risks of neurological deterioration or spinal cord injury with nonoperative management. Because surgery might reduce the risks, and early surgery was likely to be correlated with better outcomes, there was a trend toward attention to mildly symptomatic CSM. CONCLUSIONS: There is emerging enthusiasm for research on CSM worldwide, with more publications originating in Asian countries over the past few decades. The surgical management of CSM is evolving continuously toward early and anterior approaches. More prospective investigations on the optimal timing and choices of surgery are therefore needed.